Group dynamics for teams - Levi, Daniel (Thousand Oaks, California : Sage Publications, Incorporation, 2017)
Incorporating the latest research throughout, Daniel Levi's Fifth Edition of Group Dynamics for Teams explains the basic psychological concepts of group dynamics, focusing on their application with teams in the workplace. Grounded in psychology research and a practical focus on organizational behavior issues, this engaging book helps readers understand and more effectively participate in teams
Introduction -- Part I: Characteristics of teams -- Understanding teams -- Defining team success -- Part II: Processes of teamwork -- Team beginnings -- Understanding the basic team processes -- Cooperation and competition -- Communication -- Part III: Issues teams face -- Managing conflict -- Power and social influence -- Decision making -- Leadership -- Problem solving -- Creativity -- Diversity -- Part IV: Organizational context of teams -- Team, organizational, and international culture -- Virtual teamwork -- Evaluating and rewarding teams -- Team building and team training -- Appendix: Guide to Student Team Projects -- References -- Index
Includes bibliographical references and index.
Keywords: TEAMS IN THE WORKPLACE